A model for developing adolescent reproductive health behavior in urban areas - Sudarso, Sutinah, Septi Ariadi, Karnaji, Bagong Suyanto, Linggar Rama Dian Putra, Koko Srimulyo, (Opción, 2020)
This study aimed to map the health behaviors of adolescent reproductive health. This study used qualitative methods with interviews as data collection techniques. This study found that among adolescents who psychologically began to enter puberty, full of curiosity to try new things, and controlled by rising libido, certainly not an easy thing for them to be able to control attitudes of resistance, sexual desire, and behavior which tends to deviate every time. In conclusion, the most important thing is how to accommodate the potential and channel more youth energy in a variety of positive events.